A Review Paper on Torque Ripple Reduction in Brushless DC Motor Drives with Different Multilevel Inverter Topology - S. Arunkumar; S. Thangavel (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
This paper presents the overall review of torque ripple reduction techniques in brushless DC motors (BLDC) and different multilevel inverter topologies suitable for BLDC motor drives. BLDC motors are widely used for household applications due to its features of high reliability, simple frame, high efficiency, fast dynamic response, compact size and low maintenance, etc.. The switches are electronically commutated based on the information of rotor position detection. The position of the rotor is determined with the help of the sensor or sensorless techniques. Hence it is an electronically commutated motor. Because of this commutation, the ripples are generated in the electromagnetic torque and the power factor of AC mains gets affected. So, in order to improve the performance of these motors the ripple in the electromagnetic torque could be reduced and the power factor of the AC mains should be increased. An enormous review of different torque ripple reduction techniques and different multilevel inverter topologies suitable for torque ripple minimization and power quality improvement with different converter topologies are discussed. DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.6904